Analysis of The Implementation of Halal Logistics Management in Food and Beverage Retail Business (Case Study At Kopi Kenangan) - Khoirunnisa, Nur Awali; Ratih, Inayah Swasti; Almas, Bahrina (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2024)
Halal logistics management in the food and beverage industry is an integrated activity that starts from purchasing raw materials, then converting raw materials through the production process, producing finished products and finally delivering finished products to customers. Halal products are not only limited to looking clean but also need to know the process of implementing halal logistics management throughout the production process. The purpose of this study is to determine how the halal logistics management process starts from the process of supplying raw materials, processing, packaging and distribution carried out during the supply chain process to create a halal measure of a product carried out at Kopi Kenangan. The result of this study is the implementation analysis of halal logistics management at Kopi Kenangan consists of four activities: First, the production preparation process, Second, the production process, Third, the distribution process, Fourth, consumption activities. All of Kopi Kenangan products are in accordance and implement halal standardization properly in accordance with Islamic law, including production activities that do not use prohibited raw materials such as pork, dogs, blood, and khamr. All tools and places used for production and distribution activities are guaranteed cleanliness and halalness